Організаційні засади забезпечення взаємодії та координації діяльності правоохоронних органів на регіональному рівні - Русецький, А. А.; Rusetskyi, A. A. (Науковий вісник Херсонського державного університету. Сер. : Юридичні науки. – 2018. – Вип. 2, т. 3. – С. 89-92, 2018)
Визначено та розглянуто організаційні засади забезпечення взаємодії та координації діяльності правоохоронних органів на регіональному рівні. Констатовано, що сьогодні в досліджуваній сфері є досить багато недоліків, які потребуються негайного виправлення: по-перше, нині відчувається дефіцит фінансування взаємодії та координації діяльності правоохоронних органів; по-друге, недостатньо уваги приділяється навчанню працівників, особливо в контексті вивчення специфіки роботи інших правоохоронних органів; по-третє, недостатньо врегульованим є питання інформаційного забезпечення суб’єктів взаємодії. Акцентовано увагу на тому, що вирішення згаданих проблем дозволить якісно покращити стан взаємодії та координації діяльності правоохоронних органів на регіональному рівні.

The article presents a theoretical generalization and a new solution to the scientific problem, which is to determine the organizational principles for ensuring the interaction and coordination of law enforcement ac- tivities at the regional level. It is established that under the organizational principles of interaction and coordination of law-enforcement bodies at the regional level it is necessary to understand the combination of elements enshrined in the current legislation of Ukraine, which, in their unity, allow to ensure effective interaction and coordination of the ac- tivity of law-enforcement bodies at the regional level. It was emphasized that the organizational principles form the most important characteristics of the joint activities of the abovementioned bodies of state power of Ukraine. It was emphasized that the managerial decision is a “motivating” factor for the emergence of appropriate interaction and proper coordination of law enforcement agencies. It is stated that the quality and the thought of the management decision, as well as the implementation and control of its implementation, will depend directly on the effectiveness and efficiency of the interaction of law enforcement agencies at the regional level. It is noted that the general effectiveness of their work depends directly on how high-quality and profession- al personnel will be provided by law-enforcement bodies, which in turn will positively affect the effectiveness of their interaction. It is stated that today in the area under study there are many shortcomings that need immediate resolution, in particular: firstly, there is a shortage of financing of interaction and coordination of law enforcement agen- cies; secondly, insufficient attention is paid to the training of employees, especially in the context of studying the specifics of the work of other law enforcement agencies; thirdly, the issue of information provision of in- teraction subjects is not sufficiently regulated. It is emphasized that the solution of these problems will allow to improve qualitatively the state of interaction and coordination of activity of law enforcement bodies at the regional level.

Определены и рассмотрены организационные принципы обеспечения взаимодействия и координации деятельности правоохранительных органов на региональном уровне. Констатировано, что сегодня в исследуемой сфере достаточно много недостатков, которые требуются немедленного исправления: во-первых, сейчас ощущается дефицит финансирования взаимодействия и координации деятельности правоохранительных органов; во-вторых, недостаточно внимания уделяется обучению работников, особенно в контексте изучения специфики работы других правоохранительных органов; в-третьих, недостаточно урегулирован вопрос информационного обеспечения субъектов взаимодействия. Акцентировано внимание на том, что решение этих проблем позволит качественно улучшить состояние взаимодействия и координации деятельности правоохранительных органов на региональном уровне.
Organizational fundamentals of interaction and coordination of law enforcement activities at the regional level
Русецький, А. А. Організаційні засади забезпечення взаємодії та координації діяльності правоохоронних органів на регіональному рівні / Русецький А. А. // Науковий вісник Херсонського державного університету. Сер. : Юридичні науки. – 2018. – Вип. 2, т. 3. – С. 89-92.
Keywords: Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; правоохоронні органи; law enforcement agencies; правоохранительные органы; організаційні засади; organizational principles; организационные основы; регіональний рівень; regional level; региональный уровень; взаємодія; interaction; взаимодействие; координація; coordination; координация; кадрове забезпечення; personnel support; кадровое обеспечение; управлінське рішення; management decision; управленческое решение